International environmental agreements and CO₂ emissions: Fresh evidence from 11 polluting countries - Aikaterina Oikonomou; Michael Polemis; Symeoni-Eleni Soursou (Journal of Risk and Financial Management, 2021)
This study attempts to evaluate the energy and carbon footprint within the framework of international environmental treaties and the efforts made by 11 large polluting countries to mitigate climate change. The econometric methodology accounts for the presence of cross-sectional dependence while it employs second-generation panel unit root tests and cointegrated relationships. To secure the robustness of our findings, we conduct an ARDL approach employing dynamic panel data techniques. Dynamic OLS is also applied to verify the validity of the empirical results. The empirical analysis supports that the reduction in CO2 emissions can be achieved without a slowdown in economic activity for the sample countries. The findings suggest insightful policy implications for policymakers and government officials.
Keywords: 330; carbon dioxide emissions; climate change; dynamic GMM models; energy use; international agreements